Recovery of metagenome-assembled microbial genomes from a full-scale biogas plant of food waste by pacific biosciences high-fidelity sequencing - Jiang, Fan; Li, Qiang; Wang, Sen; Shen, Ting; Wang, Hengchao; Wang, Anqi; Xu, Dong; Yuan, Lihua; Lei, Lihong; Chen, Rong; Yang, Boyuan; Deng, Yu; et al. (Frontiers in Microbiology, 2023)
Background: Anaerobic digestion (AD) is important in treating of food waste, and thousands of metagenome-assembled genomes (MAGs) have been constructed for the microbiome in AD. However, due to the limitations of the short-read sequencing and assembly technologies, most of these MAGs are grouped from hundreds of short contigs by binning algorithms, and the errors are easily introduced. Results: In this study, we constructed a total of 60 non-redundant microbial genomes from 64.5 Gb of PacBio high-fidelity (HiFi) long reads, generated from the digestate samples of a full-scale biogas plant fed with food waste. Of the 60 microbial genomes, all genomes have at least one copy of rRNA operons (16S, 23S, and 5S rRNA), 54 have ≥ 18 types of standard tRNA genes, and 39 are circular complete genomes. In comparison with the published short-read derived MAGs for AD, we found 23 genomes with average nucleotide identity less than 95% to any known MAGs. Besides, our HiFi-derived genomes have much higher average contig N50 size, slightly higher average genome size and lower contamination. GTDB-Tk classification of these genomes revealed 2 genomes belonging to novel genus and 4 genomes belonging to novel species, since their 16S rRNA genes have identities lower than 95% and 97% to any known 16S rRNA genes, respectively. Microbial community analysis based on the these assembled genomes reveals the most predominant phylum was Thermotogae (70.5%), followed by Euryarchaeota (6.1%), and Bacteroidetes (4.7%), and the most predominant bacterial and archaeal genera were Defluviitoga (69.1%) and Methanothrix (5.4%), respectively. Analysis of the full-length 16S rRNA genes identified from the HiFi reads gave similar microbial compositions to that derived from the 60 assembled genomes. Conclusions: HiFi sequencing not only generated microbial genomes with obviously improved quality but recovered a substantial portion of novel genomes missed in previous short-read based studies, and the novel genomes will deepen our understanding of the microbial composition in AD of food waste.